INCREASING UTILIZATION OF PRODUCTION MACHINERY THROUGH LINE BALANCING APPROACH (CASE STUDY ON PHARMACEUTICAL INDUSTRY) - Mangapul Sitanggang; Agustinus Hariadi DP (Dinasti International Journal of Education Management And Social Science, 2021)
The growth in sales volume of unbranded generic products (considering that drugs served by BPJS Kesehatan refer to the National Formulary and e-catalogs set by the government) has led to a decline in margins as price competition intensifies. The purpose of this research is to optimize the utilization and efficiency of the machine, increase productivity and balance the line. Improvements are made by following the ECRS (Eliminating, Combining, Rearranging, and Simplify) based line balancing concept. From the improvements that have been made to the granulation process, it was found that the time of the wet mixing process, wet sieving, drying, and dry sieving had decreased. Cycle time decreased, output increase, the total granulation process time “Product F” decreased. Line efficiency increased, balance delay decreased and smoothness index decreased. This shows that the granulation line is getting more balanced